The Development Of A Green Chemistry Oriented Virtual Laboratory With Project To Improve Learning Outcomes In Teaching Of Redox Titration. - Nurul Aliyyah; Manihar Situmorang; Emitiur Malau; Mutiara Ardi (Universitas Lampung, 2026)
This study aims to develop a green chemistry-oriented virtual laboratory integrated with Project-Based Learning (PjBL) and evaluate its effectiveness in improving student learning outcomes in redox titration. The study used a Research and Development (R&D) approach with the ADDIE model and a quasi-experimental two-group pretest–posttest design. The sample consisted of 72 Chemistry Education students at Universitas Negeri Medan divided into experimental and control classes. Expert validation categorized the media as highly feasible with an average BSNP score of 3.42 in content, language, presentation, and graphics. The experimental class achieved a higher posttest score (79.55 ± 5.75) than the control class (64.55 ± 13.94). The Wilcoxon Signed-Rank Test showed a significant improvement in the experimental class (Z = -4.247, p = 0.000). The experimental class also obtained a higher N-Gain score (0.61) than the control class (0.49), with a significant difference in effectiveness (p = 0.003).